Effect of Supplementation of Monensin Sodium on rumen metabolism and Milk Yield in Early Lactating Buffalo (Bubalus Bubalus) - viraj, Prath (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was carried out to assess the effect of monensin sodium supplementation on rumen fermentation metabolites and milk yield in early lactating buffaloes. Twelve buffaloes in their 2nd week of lactation were selected. Control group was fed on standard ration whereas the treatment group was supplemented with monensin sodium @ 200 mg/head/day in addition to standard ration. Rumen liquor and blood sample was collected at 2nd and 12th week of lactation. Total and individual volatile fatty acids concentration was estimated by gas chromatography. Monensin sodium (P<0.05) decreases acetate and increases propionate concentration and decreases the ratio of acetate to propionate in the rumen liquor without altering the total volatile fatty acid concentration in experimental period. Supplemented buffaloes yielded 8.22 per cent more milk than the control. because of poor feeding practices, irregular and India has 105.1 millions buffaloes which is approximately 56.7 per cent of the total world buffalo population. They contribute 47.85 million MT of milk amounting to 55% of total milk produced in India. Although buffaloes are better converter of poor quality fibrous feeds into milk, there are few reports on low milk yield, poor reproductive performance and low growth rate inadequate availability of quality feedstuffs. Lactating dairy animals have high demand for energy and protein for milk synthesis. Mobilizing energy and protein from body tissues stores and repartition of nutrients away from extra mammary tissues are the primary alternatives source of sufficient nutrients for milk production during early lactation. Excessive utilization of body